A critical survey of predictive mathematical models for migration from packaging - Poças, Maria F. (2010)
The migration of chemicals from food contact materials into foods is an important issue in food safety.The assessment of materials compliance with regulations includes migration monitoring for many monomers and additives. However,it is recognized that predictive mathematical modelling can be used in many cases, to avoid or to reduce the effort on migration experiments. This article reviews the approaches followed to apply mathematical models to migration, particularly the models used, the approaches to estimate model parameters, and the systems used to experimentally validate the models. Conclusions on the issues requiring further research are drawn.